2020
DOI: 10.3390/ijms21207512
|View full text |Cite
|
Sign up to set email alerts
|

Multi-Omics Strategies for Decoding Smoke-Assisted Germination Pathways and Seed Vigour

Abstract: The success of seed germination and the successful establishment of seedlings across diverse environmental conditions depends on seed vigour, which is of both economic and ecologic importance. The smoke-derived exogenous compound karrikins (KARs) and the endogenous plant hormone strigolactone (SL) are two classes of butanolide-containing molecules that follow highly similar signalling pathways to control diverse biological activities in plants. Unravelling the precise mode-of-action of these two classes of mol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 116 publications
0
8
0
Order By: Relevance
“…Recent studies have reported that exogenous IAA application higher than 1 μM determines the inhibition or delay of seed germination in plants [ 33 , 34 ]. However, the mechanism of auxin action in seed germination has not been completely elucidated, although there are studies which identified the key role of interactions between IAA, abscisic acid (ABA) and even gibberellic acid (GA) to control the seed dormancy and germination [ 35 , 36 ].…”
Section: Resultsmentioning
confidence: 99%
“…Recent studies have reported that exogenous IAA application higher than 1 μM determines the inhibition or delay of seed germination in plants [ 33 , 34 ]. However, the mechanism of auxin action in seed germination has not been completely elucidated, although there are studies which identified the key role of interactions between IAA, abscisic acid (ABA) and even gibberellic acid (GA) to control the seed dormancy and germination [ 35 , 36 ].…”
Section: Resultsmentioning
confidence: 99%
“…Karrikin, which is one component of the plant-derived smoke solution [ 18 ], regulated tolerance to abiotic stresses such as drought [ 19 ] and cold [ 20 ] in Arabidopsis thaliana as well as salt [ 21 ] and cadmium [ 22 ] in oil plant. Furthermore, it was reported that the plant-derived smoke solution enhanced soybean growth under flooding [ 13 ] and after flooding [ 12 ].…”
Section: Discussionmentioning
confidence: 99%
“…Butanolides, including karrikins and cyanohydrin, are the active compounds in the plant-derived smoke solution [ 6 ]. The functional mechanisms of plant-derived smoke in the seed-germination stage were clarified with the discovery of karrikin [ 18 ]. A study on the molecular aspects of seed germination reported that abscisic acid, seed maturation, and dormancy-related transcripts were up-regulated by trimethyl butenolide and suppressed by karrikin 1, indicating that increased seed germination by karrikin 1 might be due to suppression of abscisic acid [ 6 , 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…S1, Supplementary material). Recent studies have reported that exogenous IAA application higher than 1μM determines the inhibition or delay of seed germination in plants [31,32]. However, the mechanism of auxin action in seed germination has not been completely elucidated, although there are studies which identified the key role of interactions between IAA, abscisic acid (ABA) and even gibberellic acid (GA) to control the seed dormancy and germination [33,34].…”
Section: Bioactivity Assaysmentioning
confidence: 99%